European Consumer Law Rationale in Light of New Challenges - Bublienė, Danguolė; Selvestravičiūtė, Agnė (Teisė, 2022)
This paper reviews the origin of the EU consumer protection paradigm, its development in legal doctrine and the CJEU jurisprudence, as well as the impact left on it by the insights from vulnerable consumer theory and behavioural economics discussed in the legal doctrine. The authors search for an answer whether certain social and economic challenges can be addressed within the current framework of the EU Consumer law (i.e., the Unfair Contract Terms Directive).
Keywords: consumer protection; consumer law; vulnerable consumer; Unfair Contract Terms Directive